Housing characteristics as a determinant for acute pharyngitis among toddlers - Kusumawati, Yuli; Lestari 1, Novantyas Dwi Siwi; Jalaludin, Juliana (Foundation for Enviromental Protection and Research, 2020)
Introduction: Acute pharyngitis is an inflammatory disease of the throat (pharynx) that occurs suddenly and often occurs in children. The physical house environment is suspected to be a risk factor for acute pharyngitis in toddlers. This study aimed to determine the dominant risk factors of acute pharyngitis in toddlers in the sub-district of Sangkrah Public Health Care, Surakarta, Indonesia. Methods: A case-control study conducted in children aged 12 to 59 months who suffered from acute pharyngitis disease based on doctors’ diagnosed in the Sangkrah District Public Health Centre in December 2016 until March 2017. The diagnosis of acute pharyngitis cases using McIsaac scores ≥4. The number of cases was 55 toddlers, compared with 55 controls to determine risk factors for the house environment against pharyngitis. The data were collected by questionnaire and observation checklist. Data analysis was done using SPSS version 20. Results: A total of 110 respondents were recruited into this study. The mean age of toddler in case and control group was 34.87 ± 12.99 months and 32.07 ± 14.14 months, respectively. Multiple logistic regression analysis showed that house ventilation (p = 0.009; aOR 3.273; 95% CI = 1.340-7.995) and floor condition (p = 0.022; aOR 3.053; 95% CI = 1.172-7.95) that contributed to acute pharyngitis at toddler. Conclusion: Our study reported that inadequate ventilation and not-waterproof floor condition were physical house environment risk factors the determinant factors for the occurrence of acute pharyngitis at toddlers.